1978
DOI: 10.1095/biolreprod19.3.519
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Hatching of Mouse Blastocysts in vitro by Prostaglandin Antagonists

Abstract: The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

1980
1980
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(36 citation statements)
references
References 61 publications
2
34
0
Order By: Relevance
“…Information regarding cellspecific synthesis and hydrolysis of this molecule in the uterus will be required to address this issue. Another possibility is that anandamide serves as a reservoir of arachidonic acid for the generation of prostaglandins (PGs) which are important for embryo development and implantation (39)(40)(41). This is consistent with higher levels of amidohydrolase activity and of PGE 2 in implantation sites (14,41).…”
Section: Resultsmentioning
confidence: 79%
“…Information regarding cellspecific synthesis and hydrolysis of this molecule in the uterus will be required to address this issue. Another possibility is that anandamide serves as a reservoir of arachidonic acid for the generation of prostaglandins (PGs) which are important for embryo development and implantation (39)(40)(41). This is consistent with higher levels of amidohydrolase activity and of PGE 2 in implantation sites (14,41).…”
Section: Resultsmentioning
confidence: 79%
“…In contrast, Kennedy (18) showed that in the rat PGE 2 but not PGI 2 is a key mediator of increased vascular permeability at the implantation site. Considering the fact that the blastocyst either accumulates (19) or synthesizes PGs (20,21), it has been also shown that PGs affect the glucose metabolism of preimplantation embryos (22) and hatching of the blastocysts (7).…”
mentioning
confidence: 99%
“…Indomethacin, added in vitro, may also show these actions except decreasing uterine prostaglandin synthesis. Some investigators have reported an in vitro inhibitory effect and found that indomethacin added in vitro inhibited the hatching of mouse embryo (Biggers et al 1978 ;Hurst and McFarlane 1981). The mechanism of the inhibition of hatching was considered as follows : The endogenous prostaglandins were decreased by indomethacin, so that the expansion of blastocyst could not occur (Biggers et al 1978).…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators have reported an in vitro inhibitory effect and found that indomethacin added in vitro inhibited the hatching of mouse embryo (Biggers et al 1978 ;Hurst and McFarlane 1981). The mechanism of the inhibition of hatching was considered as follows : The endogenous prostaglandins were decreased by indomethacin, so that the expansion of blastocyst could not occur (Biggers et al 1978). In order to study further the mechanism of the in vitro inhibitory effect of indomethacin on the incorporation of [3H] uridine into RNA, the incorporation rate of embryos incubated in a medium containing indomethacin and prostaglandin F2a was compared with that of embryos incubated in a medium containing indomethacin alone.…”
Section: Discussionmentioning
confidence: 99%